Evaluation of glass ionomer sealants placed according to the ART approach in a community with high caries experience: 1-year follow-up Avaliação de selantes ionoméricos realizados pela técnica do ART em comunidade com alta experiência de cárie: 1 ano de acompanhamento - Ana Luiza Falavinha Vieira; Nildiceli Leite Melo Zanella; Eduardo Bresciani; Terezinha de Jesus Esteves Barata; Salete Moura Bonifácio da Silva; Maria Aparecida de Andrade Moreira Machado; Maria Fidela de Lima Navarro (University of São Paulo, 2006)
The aim of this study was to investigate the retention rates and effect on occlusal caries incidence of two glass ionomers used as sealants, placed according to the Atraumatic Restorative Treatment (ART) approach, in a high caries-risk community. A total of 150 newly erupted first molars of 42 schoolchildren, between 6-8 years of age were selected. The teeth were divided into two groups: experimental and control groups. In the experimental group, 76 teeth were sealed using Vidrion R-SS White (conventional GIC) and in the control group, 74 teeth were sealed using ChemFlex-Dentsply (high-viscosity conventional GIC). The sealants were applied by one operator following the "press finger technique", described in the ART-WHO manual. Two calibrated independent examiners carried out the evaluation according to the ART criteria. The intra and inter-examiner agreements were 0.84 and 0.81, respectively. Data were submitted to Mann-Whitney and Chi-square tests (p<0.05). At the 1-year follow-up, 136 (90.7%) sealants were evaluated. In the control group: 28 (41.8%) of the sealants were partially or completely retained, 38 (56.7%) completely lost, and 1 (1.5%) was replaced by another treatment. In the experimental group, 30 (43.5%) of the sealants were partially or completely retained, 38 (55.1%) were clinically scored as complete loss and 1 (1.4%) were replaced by another treatment. Seven sealants in both groups were not evaluated. Secondary caries was not observed in both groups. There was no statistically significant difference between the retention (p=0.49) and effect on caries incidence rates for both groups (p=0.84). The clinical performance of the glass ionomer sealants of both groups was considered satisfactory with a high success rate (98.5%). Although the sealants placed according to the ART approach showed retention rates lower than 50% after 1 year in newly erupted first molars, this approach seems to be appropriate for communities with high caries experience. O objetivo deste trabalho foi avaliar o índice de retenção e o efeito na incidência de cárie oclusal de dois selantes ionoméricos realizados pela técnica do Tratamento Restaurador Atraumático (ART) em comunidades com alto índice de cárie. Foram selecionados 150 primeiros molares recém-erupcionados de 42 escolares, entre 6-8 anos de idade. Os dentes foram divididos em dois grupos: experimental e controle. No grupo experimental 76 dentes foram selados com Vidrion R-SSWhite (CIV-convencional) e no grupo controle, 74 dentes foram selados com ChemFlex-Dentsply (CIV-alta viscosidade). Os selantes foram realizados por apenas um operador pela técnica da "pressão digital", descrita no manual de ART da OMS. Dois avaliadores independentes e calibrados segundo os critérios do ART realizaram a avaliação. A concordância intra e inter-examinadores foi de 0,84 e 0,81, respectivamente. Os resultados foram submetidos aos testes Mann-Whitney e Q-quadrado (p<0,05). Após um ano, 136 (90,7%) selante foram avaliados. No grupo controle, 28 (41,8%) selantes estavam parcial ou completamente retidos, 38 (56,7%) completamente perdidos, 1 (1,5%) foi substituído por outro tratamento. No grupo experimental, 30 (43,5%) selantes estavam parcial ou completamente retidos, 38 (55,1%) foram classificados como completamente perdidos e 1(1,4%) foi substituído por outro tratamento. Sete selantes em ambos os grupos não foram avaliados. A presença de lesão cariosa secundária não foi observada em nenhum dos grupos. Não houve diferença estatisticamente significante entre a retenção (p=0,49) e efeito na incidência de cárie (p=0,84) entre os dois grupos. A performance clínica dos selantes ionoméricos foi considerada satisfatória com um alto índice de sucesso (98,5%). Embora os selantes aplicados de acordo com a técnica ART tenham mostrado índices de retenção abaixo de 50% depois de um ano nos primeiros molares recém-erupcionados, este método mostrou-se apropriado para comunidades com alta experiência de cárie.